A Survey on Comparisons of Cryptographic Algorithms Using Certain Parameters in WSN - Pooja Singh; R.K. Chauhan (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The Wireless Sensor Networks (WSNs) have spread its roots in almost every application. Owing to their scattered nature of sensor nodes, they are more prone to attacks. There are certain applications e.g. military, where sensor data’s confidentiality requirement during transmission is essential. Cryptography has a vital role for achieving security in WSNs.WSN has resource constraints like memory size, processing speed and energy consumption which bounds the applicability of existing cryptographic algorithms for WSN. Any good security algorithms has higher energy consumption by the nodes, so it’s a need to choose most energy-efficient cryptographic encryption algorithms for WSNs. This paper surveys different asymmetric algorithms such as RSA, Diffie-Hellman, DSA, ECC, hybrid and DNA cryptography. These algorithms are compared based on their key size, strength, weakness, attacks and possible countermeasures in the form of table.